Antioxidant Capacity as a Marker for Assessing the In Vitro Performance of the Endangered Cistus heterophyllus - Antonio López-Orenes; Antonio F. Ros-Marín; María A. Ferrer; Antonio A. Calderón (The Scientific World Journal)
Cistus heterophyllus subsp. carthaginensis is an endemic and endangered species from the SE Mediterranean coastal region of Spain. Within the framework of the efforts aiming to species conservation, in vitro culture techniques could be of interest. The aim of this study was to evaluate the antioxidant capacity of C. heterophyllus shoot cultures as a possible marker of in vitro performance. The effects of five different basal salt formulations and cytokinin levels on in vitro performance and antioxidant capacity were examined. K+/Na+ and Ca2+/Na+ ratios initially present in culture media greatly affected the antioxidant capacity (the lower the ratios the higher the antioxidant capacity). Increasing concentrations of BA resulted in higher antioxidant capacity. The results obtained point to antioxidant capacity as being a marker of incidence of stress conditions in in vitro cultured C. heterophyllus. A good correlation was found between antioxidant capacity and total soluble phenolics present in Cistus extracts. Catechin was identified in all the extracts and its levels were found to change parallel to the antioxidant capacity, pointing to a prominent role played by this flavonoid in C. heterophyllus defence against oxidative stress, which in turn affects the in vitro performance of this species.